Guar crispbread in the diabetic diet. Issue 6154 (23rd December 1978) - Jenkins, D J; Wolever, T M; Nineham, R; Taylor, R; Metz, G L; Bacon, S; Hockaday, T D
Abstract : Nine diabetic patients who were receiving various treatments supplemented their normal home diets (two patients) or metabolic ward diets (seven patients) with guar crispbread for five days. Their mean urinary glucose excretion fell significantly by 38% during the last two days. A significant fall in fasting blood glucose concentration of 1.1 +/- 0.4 mmol/1 (19.8 +/- 7.2 mg/100 ml) was seen only in those who took guar after the control period. Over eight weeks' treatment insulin dosage was reduced by 21% in five patients, and home testing showed that glycosuria was reduced by 68% in six patients. Guar crispbread is likely to be a useful adjunct to diabetic treatment irrespective of the type of treatment or insulin dosage used.